Association of lymphocyte subsets and cytokines with bone metabolism: a retrospective, cross-sectional study - Cong Peng; Qiao Yang; Xiangrui Kong; Zhengzhong Sun; Liang Wang; Li Xiao (BMC Musculoskeletal Disorders, 2024)
Abstract Background Previous research has shown that lymphocytes and cytokines can mediate bone metabolism. This study explored the clinical association and predictive ability of lymphocytes and cytokines levels for bone metabolism. Methods A total of 162 patients were enrolled in this study. The levels of N-terminal propeptide of type I procollagen (P1NP), β-collagen degradation product (β-CTX), total T lymphocytes, immature T lymphocytes, suppressor/cytotoxic T lymphocytes, helper/inducer T lymphocytes, B lymphocytes, natural killer (NK) cells, Interferon-gamma (IFN-γ), tumour necrosis factor-alpha (TNF-α), IFN-α, interleukin-1 beta (IL-1β), IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, and IL12p70 were evaluated. The relationship between these lymphocyte subsets and cytokines with bone metabolic status was examined and their predictive ability for bone metabolic status was assessed. Results The principal component analysis (PCA) and correlation analysis results varied on differences in lymphocyte subsets and cytokines in various bone metabolism states. Differential analysis revealed significant differences in the absolute counts of B lymphocytes (P < 0.05), level of IL-12p70 (P < 0.05), and IL-8 (P < 0.001) at different P1NP levels. Significant differences were observed in the absolute counts of total T lymphocytes (P < 0.05), B lymphocytes (P < 0.05), the level of IL-6 (P < 0.05), the percentage of B lymphocytes (P < 0.01), and NK cells (P < 0.05) at different β-CTX levels. Furthermore, the receiver operating characteristic (ROC) curve showed that the absolute count of B lymphocytes and levels of IL-12p70 and IL-8 could be used to evaluate bone formation states, while the absolute counts of T and B lymphocytes, level of IL-6, and percentages of NK cells and B lymphocytes could be used to evaluate bone resorption states. Conclusion The bone metabolism status changed based on the lymphocyte subsets and cytokine levels. Differentially expressed lymphocytes and cytokines could be used to distinguish bone metabolism status.